The Relationship Between the Completeness of School Facilities and Infrastructure and the Learning Achievement of Elementary School Students - Lestari, Yuyun; Gagaramusu, Yusdin; Nuraini, Nuraini; Zulnuraini, Zulnuraini; Khairunnisa, Khairunnisa (FKIP - Universitas Riau, 2025)
This research is motivated by the low learning achievement of grade V students at SD Negeri 1 Tolisu in the 2023/2024 school year. Although there are facilities and infrastructure such as computer laboratories, UKS rooms, and libraries, their use has not been maximized due to limited facilities and unsupportive room conditions. This study aims to determine the relationship between the completeness of school facilities and infrastructure and the learning achievement of grade V students at SD Negeri 1 Tolisu. The method used is descriptive quantitative with a correlational approach. The population and sample consist of all grade V students, totaling 27. Data on the completeness of facilities and infrastructure were collected through questionnaires, while learning achievement data were obtained from documentation of student report card scores. Data analysis was carried out using Pearson's product-moment correlation technique. The results showed a significant relationship between completeness of facilities and infrastructure and student learning achievement, with r calculated = 0.623 and r table = 0.381 at a 5% significance level. In addition, the t-test showed t calculated = 4.133 > t table = 1.703, reinforcing this positive relationship. These findings confirm that adequate facilities and infrastructure contribute significantly to improving student learning achievement.